Polymorphism of monogenic scab resistance loci in apple varieties - A. S. Lyzhin; N. N. Savel’eva (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. Monogenic scab resistance is an important trait of apple, useful to plant breeders. DNA markers provide a possibility to differentiate apple cultivars according to individual resistance determinants with high reliability and identify promising genotypes. The present study shows the results of the molecular genetic analysis of apple varieties, targeted at the Rvi2, Rvi4, Rvi6 and Rvi8 monogenic scab resistance loci.Materials and methods. Biological material was represented by apple cultivars of different environmental and geographical origin. Total genomic DNA was extracted from fresh leaves using CTAB methods according to the DArT protocols. The Rvi6 gene was identified with two markers, VfC (STS) and AL07 (SCAR). The presence of the Rvi4 gene was detected with the multiallelic SCAR marker AD13. The Rvi2 and Rvi8 genes were diagnosed with the SCAR marker OPL19.Results and conclusion. The Rvi6 gene was identified in 54.4% of genotypes, of which 91.9% were heterozygous, and 8.1% (cvs. ‘Svezhest’, ‘Freedom’ and ‘GoldRush’) homozygous dominant for this locus. The marker AD13-SCAR was detected in 25.0% of the studied forms (the putative genotype for the resistance gene is Rvi4Rvi4 or Rvi4rvi4). The marker OPL19-SCAR (Rvi2 and Rvi8 genes) was present in 73.5% of the analyzed forms. At least one of the studied molecular markers was present in the genome of 86.8% of genotypes. The appletree cultivars ‘Kandil Orlovsky’, ‘Krasulya’, ‘Sozvezdiye’, ‘Galarina’, ‘Priam’, ‘Redfree’ and ‘Witos’ are characterized by the combination of markers VfC, AL07-SCAR, AD13-SCAR and OPL19-SCAR in one genotype (the putative genotype for the resistance genes is Rvi2(Rvi8)Rvi4Rvi6rvi6). Cvs. ‘Antonovka zimnyaya’, ‘Antonovka krasnaya’, ‘Berkutovskoye’, ‘Geyzer’, ‘Pamyati Nesterova’, ‘Renet Simirenko’, ‘Terentyevka’, ‘Golden Delicious’, and ‘Telemon’ presumably have a homozygous recessive genotype for the studied resistance loci.